2020
DOI: 10.1186/s12913-020-05113-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of youth friendly sexual and reproductive health Services in West Gojjam Zone, north West Ethiopia: with special reference to the application of the Donabedian model

Abstract: Background: Although there has been momentum in implementing sexual and reproductive health services in Ethiopia, young people remain underserved despite their demonstrated needs. Quality care improves utilization of health service and increases the likelihood of obtaining ongoing care. However, little is known about the quality of youth-friendly sexual and reproductive health service in Ethiopia. Therefore, this study sought to investigate the quality of youth-friendly sexual and reproductive health service i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 26 publications
(25 reference statements)
2
27
0
1
Order By: Relevance
“… 62 In a 2018 study conducted in 32 primary health-care health facilities providing delivery care, the input quality was good in 66% of health facilities; however, the process and output quality was good in only 31% of health facilities. 63 Despite these challenges, there are opportunities. Quality is included in the government’s future plans; 27 the national health-care quality strategy has had promising results; 64 and the use of a community-based collaborative quality improvement initiative has improved postnatal care services in rural Ethiopia.…”
Section: Service Deliverymentioning
confidence: 99%
“… 62 In a 2018 study conducted in 32 primary health-care health facilities providing delivery care, the input quality was good in 66% of health facilities; however, the process and output quality was good in only 31% of health facilities. 63 Despite these challenges, there are opportunities. Quality is included in the government’s future plans; 27 the national health-care quality strategy has had promising results; 64 and the use of a community-based collaborative quality improvement initiative has improved postnatal care services in rural Ethiopia.…”
Section: Service Deliverymentioning
confidence: 99%
“…Recent ndings from in rural areas indicated that YFRHS provision is limited in a few of government (public) health facilities in urban centres and many youth are less informed, less experienced, and less comfortable in accessing health services in their areas. Moreover, majority of the youth often lack basic YFRHS information and knowledge about the available services, and access to affordable and con dential services [12,13,14,15,11]. Therefore, most of the youths are at a particular risk for unwanted pregnancy and pregnancy related complications [16].…”
Section: Introductionmentioning
confidence: 99%
“…countries (39)(40)(41). Adolescents in Eswatini are susceptible to gender-based violence, high fertility, and early sexual debut, and yet there are limited SRH and family planning services speci cally for Swazi youth (42).…”
Section: Discussionmentioning
confidence: 99%